DIGITAL LITERACY AS A FOUNDATION FOR RELIGIOUS MODERATION LEARNING AT SALATIGA'S AL-HIJRAH TINGKIR ISLAMIC BOARDING SCHOOL - Syaefudin Achmad (Paedagogia: Jurnal Pendidikan, 2022)
The current millennial generation, includes santri, who have digital literacy skills, but unfortunately it has not been matched by ability to use digital media to obtain information and self development. The purpose of the research was to determine the extent to which students’ digital literacy skills, how to use digital literacy as a basis for religious moderation learning, and the obstacles faced during the training on the use of digital literacy at the Al-Hijrah Islamic Boarding School Tingkir Salatiga. This research is a qualitative and participatory action research. Data collection techniques used are participant observation, interviews, and documentation. The data analysis technique uses Mile and Hubermen in the form of reduction, presentation, and conclusions. The research procedure includes planning, implementation, observation, and reflection. The result of the studi show that digital literacy can be used as a basis for learning religious moderation. The students at the Al-Hijrah Islamic Boarding School can get digital content in the form of religious moderation material from website, social media, and others. The students also take advantage of digital literacy to create religious moderation content.